Modeling PM10 in Ho Chi Minh City, Vietnam and evaluation of its impact on human health - Bang Quoc Ho (Sustainable Environment Research, 2017)
According to World Health Organization (WHO) and Global Burden of Disease, ambient air pollution is estimated to be responsible for 3.7 million premature deaths in 2012 [1]. Therefore, it is urgent to estimate the impact of air pollution on public health and economic damage. The objectives of this research are: study the distribution of PM10 concentration over Ho Chi Minh city (HCMC) and relationship to public health and for proposing solutions of diseases prevention in HCM, Vietnam. EMIssion SENSitivity model was applied to conduct air emission inventory for transportation sector. Then, Finite Volume Model and Transport and Photochemistry Mesoscale Model were used to simulate the meteorology and the spatial distribution of PM10 in HCMC. Together with disease data obtained, the US Environmental Benefits Mapping and Analysis Model was applied for calculating the number of deaths and estimating economic losses due to PM10 pollution. Finally, solutions to reduce PM10 pollution and protect public health are proposed. The results showed that the highest 1-h average concentration of PM10 is 240 μg m−3 in North Eastern of HCMC. The concentration of PM10 for annual average in District 5 ranged from 17 to 49 μg m−3. There are 12 wards of District 5 with PM10 concentration exceeding the WHO guidelines (20 μg m−3 for annual average of PM10 and 50 μg m−3 for 24-h average). The high concentration of PM10 causes 5 deaths yr−1 in District 5 and 204 deaths yr−1 in HCMC, and it causes economic losses of 1.84 billion of USD.